Experimental study on fatigue behavior of Steel Reinforced Concrete (SRC) beams. (15th September 2016) - Tong, Lewei; Liu, Bo; Xian, Qingjun; Zhao, Xiao-Ling
Highlights: Tests done on Steel Reinforced Concrete (SRC) beams under fatigue loading. The fatigue fracture of H-steel is a sign of the fatigue failure of a SRC beam. SRC composite beams have longer fatigue life than pure steel beams. Design S-N curves are proposed to H-steel and reinforcement bars inside SRC beams. Abstract: Steel reinforced concrete (SRC) beams have increasingly been adopted in civil engineering construction. There has been a paucity of studies on the fatigue behavior of SRC beams under high-cycle fatigue loading. To fill the knowledge gap in this area, this paper reports on an experimental investigation of SRC beams subjected to fatigue loading. Fatigue tests were carried out on 18 H-steel reinforced concrete beams and two pure H-steel beams. Key issues addressed in the paper include failure modes and failure sequences, crack initiation and crack propagation, as well as stiffness. The key parameters influencing the fatigue strength of SRC beams are identified, including the steel ratio of H-steel components, the steel reinforcement ratio of components and stud shear connectors. A comparison of fatigue behavior between H-steel components inside SRC beams and pure H-steel beams has been made. It seems that the fatigue failure modes of H-steel inside SRC beams are the same as those displayed by pure H-steel beams, but the former have significantly higher fatigue strength than the latter. Fatigue design (in terms of stress range – fatigue life (S-N curves)) is recommended for fatigue assessment of welded H-steel components and reinforcement components inside SRC beams, respectively.